E-Government Applications In Public Service Innovation: Study Case In Gorontalo - Syamsu Rijal; Muh. Ihsan Said Ahmad; Muhammad Islah Idrus (Journal of Research and Development on Public Policy, 2023)
Using the Gorontalo Smart Service (GSS) programme, the Gorontalo Government is attempting to raise the calibre of public services. The state apparatus's public services still have a lot of flaws, which is the context for this article. Consequently, the community's needs are still not being met to their full potential. On the other hand, many local governments must enhance a number of areas of change, including public services, if bureaucratic reform is to be sustained. In response, the Gorontalo government provided an online service application to make things simpler for the neighbourhood. With an explanation that alludes to the comprehension of the Smart City concept and bureaucratic change, this paper employs a descriptive qualitative methodology. Data is gathered through document analysis, which is then subjected to interpretive methods of analysis. According to this study, the Gorontalo government is committed to modernising public services by launching the Gorontalo Smart Service (GSS) online service application. To satisfy the demands of the bureaucratic reform agenda, which is intended to raise the calibre of public services, application innovation is undertaken. According to this study, the Gorontalo government is committed to modernising public services by launching the Gorontalo Smart Service (GSS) online service application.